(untitled) (Applied Biological Research, 2017)
High mobility, facultative diapause as pupae, rapid generation turnover, fecundity and ability to develop resistance against insecticides, make the management of Helicoverpa armigera very difficult. Entomopathogenic nematodes (EPNs) have wide host range and possess several positive attributes which make them one of the promising biocontrol agent. To establish their possible role in insect pest management, 12 EPN isolates, recovered from five districts of Uttar Pradesh (India), were used to test their virulence and biotic potential against the larvae of H. armigera. Based on morpho-molecular study they were identified as isolates of Steinernema abbasi, S. siamkayai and Heterorhabditis indica. All the tested isolates were virulent to kill H. armigera larvae within 24 to 60 h even at lowest dose (25 IJs larva-1) and produced quantifiable infective juveniles. indica isolate CH3 produced highest number of IJs (115.7±5 × 103 IJs larva-1), followed by S. abbasi isolate CS5 (100±8.5 × 103 IJs larva-1); whereas lowest was recorded from S. abbasi isolate CS3 (26.9±3×103 IJs larva-1). Cent percent mortality with short LT50 values ranging from 17.02 to 44.77 h at all concentrations proved the pathogenicity of allied steinernematids and heterorhabditids against H. armigera under laboratory conditions.